(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the pedagogical potential of teaching maqom as a form of musical heritage through structured listening activities in classroom settings. In contemporary music education, the transmission of traditional music requires methods that move beyond simple exposure and encourage active perception, interpretation, and reflection. The study examines how structured listening can support students’ understanding of maqom by guiding them to recognize musical features, respond to expressive content, and connect what they hear with broader cultural meanings. Drawing on heritage-based music pedagogy and learner-centered teaching principles, the article argues that maqom can function not only as a traditional repertoire but also as an educational resource for developing listening skills, cultural awareness, and analytical thinking. The paper proposes a classroom-oriented model in which listening tasks are organized through preparation, focused listening, guided discussion, and reflective response. This approach helps students engage with maqom in a more meaningful and accessible way, particularly in secondary school music education. The article concludes that structured listening provides an effective bridge between national musical heritage and contemporary pedagogical practice, making maqom more understandable, teachable, and relevant for young learners.